(untitled) (Docentes 2.0 Journal, 2025)
In Latin America, a new proposal aims to strengthen the process of virtual professional training inclusively in Higher Education. The objective of the research was to implement the types of inclusive spaces in a learning ecosystem proposed by the influence of the architect Rosan Bosch aimed at the educational environment and the promotion of entrepreneurship among students. The methodology used was a humanistic paradigm with a qualitative approach and a descriptive, cross-sectional case study design. The population under study was constituted by selection criteria, training 28 people with hearing disabilities, distributed with the accompaniment of teachers who are part of the Linkage with Society collective. The technique used in the study concerns a survey carried out on the participants. The prototype model was developed using the HomeByMe software that integrates digital competence with the 3D design of the construction of a space that encourages interaction and entrepreneurship in the university community. The analysis of results identifies the benefits of a digital learning ecosystem proposed in our academic center and how to replicate new environments appropriately. The conclusion emphasizes implementing training awareness programs that facilitate inclusive and effective learning for deaf students.